Methods for forecasting and preventing ice and frost deposits on power lines - Shmatov, Anton Oleksiyovych; Cherkashyna, Veronika Viktorivna (My University, 2023)
The means and technologies for predicting and preventing frost and ice deposits on the wires of overhead power lines in the power grids of foreign countries are presented. The focus is on such systems as Meteo, dynamic thermal rating (DTR), online monitoring of China Southern Power Grid, Variable resistan cecable (VRC) deicing system and mobile ice melting units. The advantages and disadvantages of these systems are analyzed and it is found that such approaches require energy consumption and are relevant only for the relevant region of the power grid, depending on weather conditions and the distance of electricity transmission.
Keywords: overheadline; powergrid; ice and frost deposition; meteorological conditions